Academic communication in higher education institutions through digital empowerment and distance learning platforms - Barkat, Abdelaziz; Selkhine, Ahmed; Agueb, Karim; Hemza, Bouraba (International journal of economic perspectives, 2024)
The implementation of the higher education quality system in Algerian universities focuses on reforming the education and training system in alignment with international standards. The primary goal is to elevate its institutions and research centers to the standards of developed countries. In the context of the digital university, digital empowerment plays a central role in the Ministry's visionary program aimed at transforming Algerian universities into knowledge-driven societies and economies, supported by technology. Digital empowerment refers to the use of digital technologies to provide individuals and communities with access to knowledge, tools, and resources that help them achieve their goals and enhance their capabilities. This study aims to explore the practical experience of distance education, which impacts all segments of society, particularly the academic environment, and to examine the challenges and prospects of distance learning in higher education institutions in Algeria. To achieve this, the study employed qualitative interviews as a data collection method, conducted with professors from the National Higher School of Management who have experience in distance education via E-learning and Google Meet platforms, both of which serve as collaborative, communicative learning environments. The findings of the study revealed several key outcomes, including the enhancement of university professors' teaching skills through training in digital media. Furthermore, digital empowerment has facilitated the acquisition of scientific knowledge and competencies via distance learning, leading to increased productivity among educators through the use of modern technology in training courses. However, these initiatives were found to be insufficient in scope, with the time allocated for training being notably short.